# Thread: Simplify Inverse Trig Function

1. ## Simplify Inverse Trig Function

Again, i had mono and got behind...thank you

Smplify the expression for f(x):

1. f(x) = sin(cos^-1(x) + sin^-1(x))

2. f(x) = tan(pi + sin^-1(x))

sorry, i am not good at typing math...thanks for all your help

2. 1. Easily done using the identities:
$\displaystyle \sin{(A \pm B)} = \sin{A}\cos{B} \pm \sin{B}\cos{A}$

$\displaystyle \sin^2{\theta}+\cos^2{\theta} = 1$

============

Let $\displaystyle \alpha = \arccos{x} \implies \cos{\alpha}=x$ and let $\displaystyle \beta = \arcsin{x} \implies \sin{\beta}=x$

$\displaystyle \sin{(\alpha + \beta)} = \sin{\alpha}\cos{\beta} + \sin{\beta}\cos{\alpha}$

$\displaystyle = \sqrt{1-\cos^2{\alpha}}\sqrt{1-\sin^2{\beta}}+\sin{\beta}\cos{\alpha}$

$\displaystyle = \sqrt{1-x^2}\sqrt{1-x^2}+x^2$

$\displaystyle = 1$

2. Recall that $\displaystyle -\tan{x} = \tan{(\pi-x)}$ and $\displaystyle \tan^2{x}+1=\sec^2{x}$

==============

$\displaystyle \tan{(\pi-(-\arcsin{x}))} = -\tan{(-\arcsin{x})}=\tan{(\arcsin{x})}$

Let $\displaystyle \alpha = \arcsin{x} \implies \sin{\alpha} = x$

$\displaystyle \tan{\alpha} = \sqrt{\frac{1}{\cos^2{x}}-1} = \sqrt{\frac{1}{1-\sin^2{\alpha}}-1}$

Simply replace and you're done.